Brute force on 10 letters - Kovács, Zoltán; Hudi, István (Teaching Mathematics and Computer Science, 2007)
We deal with two problems in the set of 10-character-long strings. Both problems can be solved by slightly different methods, but our approach for each is brute force. As we point out, there can be differences in effectivity even in different brute force algorithms. As an additional result, we answer an open question of Raymond Smullyan’s.